UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) SISWA KELAS VA SD NEGERI 27 NEGERI SEBANGAR KECAMATAN MANDAU KABUPATEN BENGKALIS - Nasution, Susilawati; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This research was conducted because of the result of learning Mathematic class VA SD Negeri 27 Sebangar. From 18 student who achieve KKM just 8 student (44,44%) while student who did’nt complete 11 student (55,56 %) with an average of 55,83. This research aims to increase learn result mathematic year school 2015-2016. This reaserch subject are student class V SD Negeri 27 Sebangar Kecamatan Mandau kabupaten Bengkalis. This matter can prove with the acquisition score teacher activity experience increase one cycle first appointment teacher activity presentation are 62,5% with the good caregory grow up to 12,5% to 75% with the good category. And than 2 cycle on the first appointment increase again 8,3% to 88,3 with the excellent category and the second appointment increase again 8,4% to 91,7%with the excellent category. So do with the student activity one cycle first appointment student presentation are 54,2% with the enough category grow up 8,3 to 62,5 with the good category. On the second appointment and than 2 cycle first appointment 12,5% to 75% with the excellent category the second appointment increase again 12,5% to 87,5% with the excellent category. With the increased teacher and student activity each appointment positive effect to increased study result student. It can see from the acquisition average basic 56,88 increase to daily exam one cycle average 88,05 and can increase again daily II, 2 cycle average 89,53. Therefore can conculuded that hypothesis in this research can applied to leaning model cooperative type TAI can increased study result Mathematic student class V SD Negeri 27 Sebangar Kecamatan Mandau Kabupaten Bengkalis.  Key Words: Team Assisted Individualization, Learning Outcomes Mathematics